Implementation of Pirates VS Echinomonster Algebra Props To Improve Math Learning Outcomes - Fariyanti, Deby; Lutfiyah, Lutfiyah; Hidayatin, Nur (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2024)
This research attempts to determine student learning results through the utilization of mathematical concepts and pirates vs. echinomonster props. This study is a qualitative, descriptive research project. The subject of this lesson is algebra. The study's subjects were five female students from SMP Al Kholili Kalisat Jember's class VII for the 2023–2024 academic year. The procedures of tests and interviews are employed in this research to collect data. Strategies for data analysis in this study are based on looking at how students tackle algebraic problems. The results showed that kids could solve algebraic problems with pirates vs. echinomonster props. The employment of pirates vs. echinomonster algebra props has been shown to improve students' mathematical learning outcomes by 1.2%, according to the study's findings.